Simple criteria and indicators to uncover and negotiate local perceptions on sustainability - Tiani, A.M.; Charancle, J.M. B. (2007)
Simple Criteria and Indicators (C&I – to be read as C and Is) can be used to help forest people express their view on sustainability. Three main findings characterize local perceptions: a) The natural and social worlds are intertwined, confirming environmental services as elements of well-being; b) The C&I often express lacking factors, uncertainties and apprehensions, thus they are naturally dynamic, and could be efficient as tools to monitor and evaluate social changes; c) The variability of interests and motivations of different social groups that make up a community is mitigated by a convergence of vision related to social capital, land security, resource management, and quality of life. The authors conclude that prior identification of the C&I through a systematic process will allow development projects to be more adapted to communities’ specific needs and to increase community support and involvement.